2017
DOI: 10.18203/2349-3291.ijcp20170070
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of congenital heart disease in a tertiary care centre of Eastern India

Abstract: Background: Congenital heart disease (CHD) is not an uncommon entity in our country. The prevalence of CHD is 9.3 per 1000 life birth in Asia which is found to be highest globally. Not much of Indian data is available particularly from this part of the country. So we conduct a retrospective study to know the spectrum of congenital heart disease in our set up.Methods: This is a retrospective hospital based study carried out over a period of 20 months (2015 March - 2016 November) where all suspected children (&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 3 publications
4
15
1
Order By: Relevance
“…Most of CHDs were diagnosed between 1 month and 6 years (69.2%), which is comparable to other studies. 12 The highest number of cases was seen between 1 month and 6 years of age which could be because of a large number of referrals from peripheral health center and increasing use of echocardiography. In present study, CHDs were more common among the male 1250 (60.32%), with a male-tofemale ratio of 1.52:1.…”
Section: Discussionmentioning
confidence: 99%
“…Most of CHDs were diagnosed between 1 month and 6 years (69.2%), which is comparable to other studies. 12 The highest number of cases was seen between 1 month and 6 years of age which could be because of a large number of referrals from peripheral health center and increasing use of echocardiography. In present study, CHDs were more common among the male 1250 (60.32%), with a male-tofemale ratio of 1.52:1.…”
Section: Discussionmentioning
confidence: 99%
“…Male: Female ratio was 3.6: 1. In a study by Mahapatra A et al, where among 231 patients with CHD, CHD were more common among males (54.5%) with the male to female ratio is 1.2:1 [33]. In this study majority of patient that is 36 neonates presented in between age of 16-28 days of age (48%).…”
Section: Discussionmentioning
confidence: 45%
“…2 patients (2.7%) presented with shock. Mahapatra A et al, showed out of 231 of his study patients 196 had murmurs, 96 had tachycardia, 84 had tacyhpnea, 28 had clubbing, 21 had oedema, 41 had enlarged liver [33]. Chest X-ray findings were oligaemic lung in 39%, plethoric lung in 44%, cardiomegaly in 46%, egg on side shaped heart in 14% patients and boot shaped heart was found in 5% patients.…”
Section: Discussionmentioning
confidence: 91%
“…The maximum no. of children were less than 6 months of age (48.2%).According to a study conducted in Odisha, India by Dr Mahapatra A. et al [9] ,this is the most common congenital heart disease in India accounting for 36.3%. 91 % (51cases) patients in this study group had increased pulmonary vascular markings in their chest x-ray which is very characteristic in ventricular septal defect as pulmonary blood flow is increased in VSD.…”
Section: Discussionmentioning
confidence: 98%